Impact of short stature on quality of life: A systematic literature review. (April 2021) - Backeljauw, Philippe; Cappa, Marco; Kiess, Wieland; Law, Lisa; Cookson, Charlotte; Sert, Caroline; Whalen, John; Dattani, Mehul T.
Abstract: Objective: We sought to obtain a better understanding of the burden of short stature using a systematic literature review. Methods: Studies of the burden of short stature, of any cause in adults and children, were searched using Embase, MEDLINE and Cochrane databases in April 2020, capturing publications from 2008 onwards. Case series and populations with adult-onset growth hormone deficiency (GHD) were excluded. Results: Of 1684 publications identified, 41 studies (33 in children, 8 in adults) were included. All studies assessed human burden. Most study populations in children included short stature due to GHD, idiopathic short stature (ISS) and short stature after being born small for gestational age (SGA). In these populations, four studies showed that quality of life (QoL) in children with short stature was significantly worse than in children with normal stature. A significant association between QoL and short stature was observed in children with chronic kidney disease (CKD) (3 studies), achondroplasia (1 study) and transfusion-dependent β-thalassaemia (1 study), and in samples with mixed causes of short stature (3 studies). Three studies (one in GHD/ISS/SGA and two in CKD) found no significant association between short stature and QoL, and several studies did not report statistical significance. Approximately half of adult studies showed that QoL was reduced with short stature, and the other half showed no association. Two studies, one in adults with Prader–Willi syndrome and one in children with GHD, suggested a potential association between short stature and poorer cognitive outcomes. Three studies demonstrated an increased caregiver burden in parents of children with short stature. Conclusions: Evidence suggests that, compared with those with normal stature, children and adults with short stature of any cause may experience poorer QoL. Further research could extend our understanding of the human burden in this field. Highlights: Short stature in children may have a negative impact on quality of life. Parents of children with short stature may experience increased caregiver burden. The negative impact of short stature on quality of life may persist into adulthood.